The influence of corporate governance on enterprise risk management (ERM) and its effect on shareholders value maximising: Malaysian shariah-compliant firms / Enny Nurdin Sutan Maruhun - Nurdin Sutan Maruhun, Enny (2019)
The governance of companies has been the subject of increasing interest following the global financial crisis. Enterprise risk management (ERM) was introduced as a response to an increasing pressure received by organizations to manage risks comprehensively and to enhance the firm value that was diminishing during the crisis. Despite the claim that ERM is the solution for corporate governance deficiency, particularly in risk management practices and its potential of value creation, the number of empirical research studying this new field is still limited. Thus, this study aimed at assessing the current extent of ERM practices, identifying factors that influence ERM implementation and examining the impact of ERM to firm value among Malaysian Shariah-compliant public-listed companies. ERM implementation was measured by using ERM Dimension index (ERMDi). ERMDi was developed due to the limitation of ERM dimension that are highlighted in the literatures. A questionnaire survey was designed based on ERMDi to assess the current stage of ERM practices. Shareholders value maximising theory and agency theory were used as the theoretical foundation to examine the determinants of ERM implementation. Shareholders value maximising theory was proxied by three variables that are financial distress cost, underinvestment problems and Tobin’s Q.